C-terminal activating and inhibitory domains determine the transactivation potential of BSAP (Pax-5), Pax-2 and Pax-8. - Dörfler, P (1996)
Pax-5 encodes the transcription factor BSAP which plays an essential role in early B cell development and midbrain patterning. In this study we have analysed the structural requirements for transcriptional activation by BSAP. In vitro mutagenesis and transient transfection experiments indicate that the C-terminal serine/threonine/proline-rich region of BSAP contains a potent transactivation domain of 55 amino acids which is active from promoter and enhancer positions. This transactivation domain was found to be inactivated by a naturally occurring frameshift mutation in one PAX-5 allele of the acute lymphoblastic leukemia cell line REH. The function of the transactivation domain is negatively regulated by adjacent sequences from the extreme C-terminus. The activating and inhibitory domains function together as an independent regulatory module in different cell types as shown by fusion to the GAL4 DNA binding domain. The same arrangement of positively and negatively acting sequences has been conserved in the mammalian Pax-2 and Pax-8, the zebrafish Pax-b as well as the sea urchin Pax-258 proteins. These data demonstrate that the transcriptional competence of a subfamily of Pax proteins is determined by a C-terminal regulatory module composed of activating and inhibitory sequences.